A candidate super-Earth planet orbiting near the snow line of Barnard’s star - Ribas, Ignasi; Trifonov, Trifon; Quirrenbach, Andreas; Henning, Thomas; Kaminski, Adrian; Reffert, Sabine; Seifert, Walter; Tsapras, Yiannis (Nature, 2018)
Analysis of 20 years of observations of Barnard’s star from seven facilities reveals a signal with a period of 233 days that is indicative of a companion planet.